Atmospheric and Aerosol Chemistry - McNeill, V. Faye.; Ariya, Parisa A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Christian George, Barbara D$1 (BAnna, Hartmut Herrmann, Christian Weller, Veronica Vaida, D. J. Donaldson, Thorsten Bartels-Rausch, Markus Ammann Emerging Areas in Atmospheric Photochemistry Lisa Whalley, Daniel Stone, Dwayne Heard New Insights into the Tropospheric Oxidation of Isoprene: Combining Field Measurements, Laboratory Studies, Chemical Modelling and Quantum Theory Neil M. Donahue, Allen L. Robinson, Erica R. Trump, Ilona Riipinen, Jesse H. Kroll Volatility and Aging of Atmospheric Organic Aerosol P. A. Ariya, G. Kos, R. Mortazavi, E. D. Hudson, V. Kanthasamy, N. Eltouny, J. Sun, C. Wilde Bio-Organic Materials in the Atmosphere and Snow: Measurement and Characterization V. Faye McNeill, Neha Sareen, Allison N. Schwier Surface-Active Organics in Atmospheric Aerosolss
Emerging Areas in Atmospheric Photochemistry -- New Insights into the Tropospheric Oxidation of Isoprene: Combining Field Measurements, Laboratory Studies, Chemical Modelling and Quantum Theory -- Volatility and Aging of Atmospheric Organic Aerosol -- Bio-Organic Materials in the Atmosphere and Snow: Measurement and Characterization -- Surface-Active Organics in Atmospheric Aerosols.
Keywords: Chemistry; Chemistry, Physical organic; Chemistry; Physical Chemistry; Atmospheric Sciences; Geophysics and Environmental Physics